2020
DOI: 10.1186/s12920-020-00744-7
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA profiling of pediatric Medulloblastoma

Abstract: Background Medulloblastoma (MB) is one of the most common malignant cancers in children. MB is primarily classified into four subgroups based on molecular and clinical characteristics as (1) WNT (2) Sonic-hedgehog (SHH) (3) Group 3 (4) Group 4. Molecular characteristics used for MB classification are based on genomic and mRNAs profiles. MB subgroups share genomic and mRNA profiles and require multiple molecular markers for differentiation from each other. Long non-coding RNAs (lncRNAs) are more than 200 nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…Our result indicated that interaction pairs of MIR181A2HG-FOXP2-hsa-miR-146b-3p may be associated with PTC. e expression of BLACAT1 is increased in some cancers, such as medulloblastoma, colon adenocarcinoma, pancreatic adenocarcinoma, gastric cancer, and TC [30][31][32][33][34][35]. Moreover, BLACAT1 has a prognostic value for patients with PTC [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our result indicated that interaction pairs of MIR181A2HG-FOXP2-hsa-miR-146b-3p may be associated with PTC. e expression of BLACAT1 is increased in some cancers, such as medulloblastoma, colon adenocarcinoma, pancreatic adenocarcinoma, gastric cancer, and TC [30][31][32][33][34][35]. Moreover, BLACAT1 has a prognostic value for patients with PTC [36].…”
Section: Discussionmentioning
confidence: 99%
“…LBX2-AS1 is upregulated in PTC and TC [37]. MIR100HG is downregulated in pediatric medulloblastoma [31]. In gastric cancer, downregulation of MIR100HG inhibits cell proliferation and migration [40].…”
Section: Discussionmentioning
confidence: 99%
“…There is a pressing need to identify the underlying molecular pathways in these subgroups in order to promote precision medicine-based therapies, improve quality of life, and expand our overall understanding of MB (122). By searching Gene Expression Omnibus (GEO) database for MB related microarray datasets, Kesherwani and colleagues determined the prognostic relevance of lncRNAs and the distinct lncRNAs associated with each MB subgroup (123). Through a joint analysis of the RNA-seq data from the European Genome-Phenome Archive (EGA) and two studies of MB from GEO, the research team from Johns Hopkins University identified 17 putative candidate lncRNAs that could be used as progression or as diagnostic and prognostic biomarkers (124).…”
Section: Medulloblastoma (Mb)mentioning
confidence: 99%
“…One of these studies validated the top 10 oncogenic or tumor suppressive lncRNAs in each MB subgroup and explored their associated molecular pathways. Among these identified lncRNAs, high expression of HAND2-AS1 in WNT-MB, low expression of MEG3 in SHH-MB, high expression of DLEU2 and DSCR8 in group 3 MB, and high expression of DLEU2 and low expression of XIST in group 4 were associated with poor prognosis [ 183 ]. In this manner, lncRNAs may be exploited as prognostic biomarkers for molecular identification of MB subgroups.…”
Section: Non-coding Rnas In Mbmentioning
confidence: 99%